Cell biological mechanisms of activity-dependent synapse to nucleus translocation of CRTC1 in neurons - Ch'ng, Toh Hean; DeSalvo, Martina; Lin, Peter; Vashisht, Ajay; Wohlschlegel, James; Martin, Kelsey (Frontiers in Molecular Neuroscience, 2015)
Previous studies have revealed a critical role for CREB-regulated transcriptional coactivator (CRTC1) in regulating neuronal gene expression during learning and memory. CRTC1 localizes to synapses but undergoes activity-dependent nuclear translocation to regulate the transcription of CREB target genes. Here we investigate the long-distance retrograde transport of CRTC1 in hippocampal neurons. We show that local elevations in calcium, triggered by activation of synaptic glutamate receptors and L-type voltage-gated calcium channels, initiate active, dynein-mediated retrograde transport of CRTC1 along microtubules. We identify a nuclear localization signal within CRTC1, and characterize three conserved serine residues whose dephosphorylation is required for nuclear import. Domain analysis reveals that the amino-terminal third of CRTC1 contains all of the signals required for regulated nucleocytoplasmic trafficking. We fuse this region to Dendra2 to generate a reporter construct and perform live-cell imaging coupled with local uncaging of glutamate and photoconversion to characterize the dynamics of stimulus-induced retrograde transport and nuclear accumulation.